2022
DOI: 10.1371/journal.pone.0275388
|View full text |Cite
|
Sign up to set email alerts
|

Individual costs and community benefits: Collectivism and individuals’ compliance with public health interventions

Abstract: Differences in national responses to COVID-19 have been associated with the cultural value of collectivism. The present research builds on these findings by examining the relationship between collectivism at the individual level and adherence to public health recommendations to combat COVID-19 during the pre-vaccination stage of the pandemic, and examines different characteristics of collectivism (i.e., concern for community, trust in institutions, perceived social norms) as potential psychological mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 56 publications
(95 reference statements)
0
14
0
Order By: Relevance
“…We may assume that enforcing a physical distance of 1.5–2 m and promoting the absence of interpersonal touch can represent a particularly serious challenge in some regions, especially in those highly valuing close social contacts (Creighton et al, 2022). On the other hand, the body of literature in this area generally finds that collectivism, which is also associated with a high value of interpersonal closeness, generally predicts greater COVID-19 protection compliance (Cho et al, 2022; Im & Chen, 2022; Leong et al, 2022; Lu et al, 2021), and higher self-importance/expectation to engage in behaviors known to prevent the COVID-19 spread (Cho et al, 2022). This trend may be driven by collectivism being associated with a belief that other members of a community consider it important to engage in preventive behaviors (Cho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…We may assume that enforcing a physical distance of 1.5–2 m and promoting the absence of interpersonal touch can represent a particularly serious challenge in some regions, especially in those highly valuing close social contacts (Creighton et al, 2022). On the other hand, the body of literature in this area generally finds that collectivism, which is also associated with a high value of interpersonal closeness, generally predicts greater COVID-19 protection compliance (Cho et al, 2022; Im & Chen, 2022; Leong et al, 2022; Lu et al, 2021), and higher self-importance/expectation to engage in behaviors known to prevent the COVID-19 spread (Cho et al, 2022). This trend may be driven by collectivism being associated with a belief that other members of a community consider it important to engage in preventive behaviors (Cho et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…For example, need dissatisfaction was negatively related with support for anti-pandemic behaviors in China; however, in countries where epidemic prevention and control were loosened, would their citizens blame need dissatisfaction on loosened policies and then support anti-pandemic behaviors? Moreover, since there are many differences in cognition, attitudes, and behaviors between individualistic and collectivistic cultures ( Lu et al, 2021 ; Leong et al, 2022 ), and now-oriented and future-oriented cultures ( Goldberg, 1976 ), cultural differences in the relationship and mechanism between need dissatisfaction and compliance should be considered and explored in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, results on institutional trust and compliance behaviors varied (see Rudert et al, 2021 for a review). Leong et al (2022) found that for collectivistic individuals in Slovakia, perceived social norms could explain compliance with public health interventions, but institutional trust could not. Caplanova et al (2021) also found that institutional trust did not have a statistically significant effect on compliance with face-covering measures.…”
Section: Introductionmentioning
confidence: 97%
“…The study had several limitations. First, as this study was centered in China, the applicability of the results in other countries or cultures should be investigated as there are many differences in cognition, attitudes, and behaviors between individualistic and collectivistic cultures (Gallè et al, 2021;Leong et al, 2022;Lu et al, 2021aLu et al, , 2021b, and now-oriented and future-oriented cultures (Goldberg, 1976). Cultural differences in the relationship and mechanism between need dissatisfaction and compliance as well as cultural factors affecting compliance behaviors (Kitayama et al, 2022) should be considered and explored in future studies.…”
Section: Limitationsmentioning
confidence: 99%